FINANCIAL REPORTING DENGAN REPUTASI AUDITOR SEBAGAI VARIABEL MODERASI ATAS PROFITABILITAS, LEVERAGE DAN UMUR PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2015) - Martinho Soares; M. Nuryatno Amin (Jurnal Magister Akuntansi Trisakti, 2016)
The purpose of this research is to find empirical evidence about the analysis of the factors that affect the timeliness of financial reporting by the auditor’s reputation as a moderating variable on profitability, leverage and firm age.The research sample in the manufacturing company listed on the Indonesia Stock Exchange on 2010-2015. Sample selection method used this research is purposive sampling method, choosing a sample based on criteria selection to provide information to researchers. A total of 38 samples were selected based on this sample selection method. The analytical method used in this research is the logistic regression method.The analysis technique used logistic regression analysis with SPSS 22 software. Based on these results can conclude that (1) profitability positively affects the timeliness of financial reporting, (2) leverage does not affect the timeliness of financial reporting, (3) firm age does not affect the timeliness of financial reporting, (4) audit delay negatively affects the timeliness of financial reporting, (5) firm size does not affect the timeliness of financial reporting, (6) internal auditor does not affect the timeliness of financial reporting, (7) reputable auditorscannot moderate the effect of profitability on the timeliness of financial reporting, (8) reputable auditorscannot moderate the effect of leverage the timeliness of financial reporting, and (9) reputable auditorscannot moderate effect the firm  age on the timeliness of financial reporting.